2020
DOI: 10.1371/journal.pone.0233266
|View full text |Cite|
|
Sign up to set email alerts
|

Automatic hoof-on and -off detection in horses using hoof-mounted inertial measurement unit sensors

Abstract: For gait classification, hoof-on and hoof-off events are fundamental locomotion characteristics of interest. These events can be measured with inertial measurement units (IMUs) which measure the acceleration and angular velocity in three directions. The aim of this study was to present two algorithms for automatic detection of hoof-events from the acceleration and angular velocity signals measured by hoof-mounted IMUs in walk and trot on a hard surface. Seven Warmblood horses were equipped with two wireless IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…The first novel method estimated hoof-on and -off using Acc R of either the pastern (M1 p ) or cannon (M1 c ). At the level of the hoof, peaks in Acc R are created by the hoof-surface impact (hoof-on) and subsequent hoof lift-off (hoof-off) [13]. Here, it is hypothesised that these peaks in acceleration, which correspond to the gait events, would be detectable at the more proximal locations of the pasterns and cannons.…”
Section: Alternative Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first novel method estimated hoof-on and -off using Acc R of either the pastern (M1 p ) or cannon (M1 c ). At the level of the hoof, peaks in Acc R are created by the hoof-surface impact (hoof-on) and subsequent hoof lift-off (hoof-off) [13]. Here, it is hypothesised that these peaks in acceleration, which correspond to the gait events, would be detectable at the more proximal locations of the pasterns and cannons.…”
Section: Alternative Methodsmentioning
confidence: 99%
“…The second novel method estimated hoof-on and -off using AngVel R recorded at the pastern (M2 p ) mounted sensors. Tijssen et al [13] reported that spikes in AngVel R recorded at the hoof coincide with hoof-on and -off. Here, the hoof wall can be considered a rigid structure meaning there would be no angular movement of the hoof relative to the solid ground during stance phases.…”
Section: Alternative Methodsmentioning
confidence: 99%
See 3 more Smart Citations